Analysis of coke gas properties at operation of its metering systems - Dzhyhyrei, Viktor; Matiko, Fedir (Lviv Polytechnic Publishing House, 2016)
The generalization and analysis of coke oven gas composition using the data of literary sources and coke enterprises are carried out in the paper. The range of pressure and temperature of coke gas during transportation is defined. The physical properties of coke gas (density, compressibility factor, adiabatic index, dynamic viscosity) that are the part of the equation of gas flowrate by method of variable differential pressure are investigated in the defined range of pressure and temperature. 25 gas mixtures with different composition were synthesized in order to make the analysis of dependency of physical properties versus pressure, temperature and composition of the mixtures. According to the results of the research the recommendations for the development of simplified methods for calculating the physical properties of coke oven gas are made.
Keywords: mixture; coke gas; physical properties; density; compressibility factor; adiabatic index; dynamic viscosity